Dispersive Solid Phase Extraction Using Magnetic NanoparticlesPerformed in a Narrow-Bored Tube for Extraction of Atorvastatin,Losartan, and Valsartan in Plasma - Mir Ali Farajzadeh; Adeleh Yadeghari; Maryam Abbaspour (Tabriz University of Medical Sciences, 2019)
Purpose: In this investigation, a new version of magnetic solid phase extraction (MSPE) performedin a narrow-bore tube has been proposed. In this study, hydrophobic octyl (C8) functionalizedFe3O4 magnetic nanoparticles (MNPs) stabilized by SiOH groups (Fe3O4@SiO2@C8) are used asmagnetic nano-sorbents for the extraction of cardiovascular drugs from human plasma prior totheir determination by high performance liquid chromatography-photodiode array detection.Methods: After precipitation of the plasma proteins, the supernatant is diluted with deionizedwater and filled into the narrow-bore tube. Then mg-level of the sorbent is added into the tube.The sorbent is dispersed and moved down through the solution instead of passing the solutionfrom the cartridge. Using an external magnet, the collected nano-sorbents at the bottom of thetube are transferred on top of the solution and released to move down through the solution forthree times to increase the extraction efficiency.Results: The linearity of the assay was ranging from 0.4-500 mg mL-1. The limits of detectionand quantification of the method were obtained in the ranges of 0.05-0.07 and 0.16-0.24 mgL-1, respectively. The extraction recoveries were obtained in the range of 31-49%. Intra- andinter-day precisions were calculated and obtained in the ranges of 5-8 and 7%-9% for 0.5 mgL-1 of each analyte, and 5-6 and 6%-8% for 2 mg L-1 of each analyte, respectively.Conclusion: The proposed method was successfully used in determination of the studied drugsin patient's plasmas.